If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying M + 70 = 81 Reorder the terms: 70 + M = 81 Solving 70 + M = 81 Solving for variable 'M'. Move all terms containing M to the left, all other terms to the right. Add '-70' to each side of the equation. 70 + -70 + M = 81 + -70 Combine like terms: 70 + -70 = 0 0 + M = 81 + -70 M = 81 + -70 Combine like terms: 81 + -70 = 11 M = 11 Simplifying M = 11
| (4x-5y)(64x^2-20xy+25y^2)= | | (4x-5y)(64x^2+20xy+25y^2)= | | 5r+30/15=2r-12/2 | | 5x^2-13xy+6y^2=0 | | X/7+x/8=15/56 | | x(3x-6)=(3x+6)(x-5) | | 2=4(x-4)-(x-6) | | 7x-4=4x-55 | | 16t^2+96= | | 5x-(2x+3)=15 | | 8x-3=4x-51 | | 135x-17=126x+18 | | 15x=20x-80 | | 17=-9x+12/6 | | 4x-2(2-2x)=6x-2 | | 6a-5=23-2g | | 12x-91=-3 | | 4ln(x-6)=-4 | | 7x+2=3w+94 | | (x-3)^1/2+2x=42 | | .7(34)+34= | | .7(.7)+34= | | .8x=.3+.6x | | -18(9)+9y=-43 | | b=a+(n-1) | | -18(-18)+9y=-43 | | 1.4(-1.3)-1.3y=-6.3 | | 1.4(1.4)-1.3y=-6.3 | | -3y=18 | | -1.8(1.6)+1.6y=-7.9 | | 14y-16y=48 | | -1.8(.6)+1.6y=-7.9 |